The Aesthetic Function of Art - Iseminger, Gary (Book collections on Project MUSE., 2018)
How can we understand art and its impact? Gary Iseminger argues that the function of the practice of art and the informal institution of the artworld is to promote aesthetic communication. He concludes that the fundamental criteria for evaluating a work of art as a work of art are aesthetic. After considering other practices and institutions that have aesthetic dimensions and other things that the practice of art does, Iseminger suggests that art is better at promoting aesthetic communication than other practices are and that art is better at promoting aesthetic communication than it is at anything else. Iseminger bases his work on a distinction often blurred in contemporary aesthetics, between art as a set of products"works of art"and art as an informal institution and social practice--the artworld. Focusing initially on the function of the artworld rather than the function of works of art, he blends elements from two of the most currently influential philosophical approaches to art, George Dickie's institutional theory and Monroe Beardsley's aesthetic theory, and provides a new foundation for a traditional account of what makes good art.